Persuasive Rhetoric in Goodluck Jonathan’s 2011 Presidential Political Campaign Advertisements in Nigeria (2016)
This study explored the rhetorical appeals expressed in Goodluck Jonathan's 2011 presidential political adverts and their influence on voting decisions of Nigerian voters during the election. Quantitative and qualitative research methods were employed for data gathering and analysis. The multistage and simple random sampling techniques were used to delineate Ibadan North Local Government into wards and to select two communities, while the purposive sampling technique was used to select respondents of voting age, those who could recall the presidential political adverts and who also voted for Jonathan during the 2011 presidential elections. Data were gathered from three hundred and nine (309) participants' duly completed copies of the questionnaire and structured interviews conducted with a political activist and a media practitioner. Survey data were analysed through simple percentages and Pearson correlation, while the video advertisements were analysed using the rhetorical parameters: ethos, pathos and logos. Respondents have positive perception of Goodluck Jonathan's personality in the adverts which influenced their decision to vote him as president in 2011. Goodluck Jonathan's credibility, as shown in the adverts, significantly influenced the voters' emotion (pathos) (r = 0.469; p<0.05) and their sense of reasoning (logic) (r = 0.624; p<0.05) in voting him. The logical appeal in the adverts significantly influenced voters more than the emotional appeal (p<0.05). There is no significant difference in genders' perceptions about Jonathan's political adverts. Hence, there is need to further explore the use of rhetoric in political advertising in order to design appropriate strategies backed with appropriate messages that will persuade the audience for a reciprocal action.